Demands and Resources in Retail: The Role of Occupational Status and COVID-19 - Ström, Philip; Falkenberg, Helena; Pienaar, Jacobus; Leineweber, Constanze; Sverke, Magnus (Nordic Journal of Working Life Studies, 2025)
Challenges related to mental health and staff retention are common in the retail industry and were likely accentuated during COVID-19. This study used questionnaire data from Swedish retail employees (N = 388) to investigate whether job demands and resources differed based on occupational status and a crisis like the pandemic. Mean levels and associations with job satisfaction, turnover intention, and burnout were compared between blue-collar and white-collar employees, before and during the pandemic. Blue-collar employees reported greater physical demands, lower levels of resources, and higher levels of burnout. Job insecurity and emotional demands increased during the pandemic, especially for blue-collar employees. Overall, job demands and resources predicted outcomes in line with previous literature, but job insecurity was particularly salient for blue-collar employees, and autonomy for white-collar employees. Crises like the pandemic affect job demands and resources, potentially exposing lower occupational status employees to a higher risk for negative consequences such as burnout.